Energetic Magnetospheric Particle Fluxes Onto Callisto's Atmosphere. Issue 11 (23rd November 2022) - Liuzzo, Lucas; Poppe, Andrew R.; Addison, Peter; Simon, Sven; Nénon, Quentin; Paranicas, Christopher
Abstract: This study investigates how Callisto's perturbed electromagnetic environment—generated by the moon's interaction with the low‐energy Jovian magnetospheric plasma—affects the dynamics of high‐energy ions and electrons. We constrain how these perturbed fields influence the energetic particle fluxes deposited onto the top of Callisto's atmosphere between energies of 4.5 keV ≤ E ≤ 11.8 MeV. We use a hybrid simulation to model the variability in Callisto's perturbed electromagnetic environment over a synodic period by considering three representative scenarios of the moon's plasma interaction, corresponding to various distances of the moon to the Jovian magnetospheric current sheet. The local field perturbations are maximized near the center of the sheet (forming, e.g., signatures of field‐line pileup, draping, and Alfvén wings) whereas far from the sheet, a mere superposition of the moon's induced dipole with the background field largely explains the perturbations. We then apply a test‐particle approach to investigate the dynamics of energetic electrons and ions (protons, oxygen, and sulfur) while exposed to these fields. Since electron gyroradii are smaller than Callisto, the field perturbations generate small‐scale non‐uniformities in their flux patterns onto the moon, while the ion flux patterns are more homogeneous. Energetic electrons dominate the number flux onto the atmosphere, whereas ions dominate the energy flux. Over a synodic period, the flux patterns onto Callisto's exobase closely resemble those when the moon is near the current sheet center, since the differential energetic particle fluxes in the ambient plasma decrease by an order of magnitude when the moon travels far outside of the sheet. Plain Language Summary: Callisto's ambient plasma environment is comprised of low‐ and high‐energy particles from Jupiter's magnetosphere that continually bombard the moon. Callisto's interaction with the low‐energy population generates currents that locally perturb the electric and magnetic fields, the structures of which vary periodically over a full rotation of Jupiter. These perturbed electromagnetic fields, in turn, strongly affect the dynamics of the high‐energy population—particles that are responsible for partially ionizing Callisto's atmosphere and sputtering the icy surface. This study constrains the degree to which these energetic ions and electrons are affected by Callisto's perturbed electromagnetic environment. We investigate how the high‐energy irradiation of Callisto's atmosphere varies not only with latitude and longitude, but also throughout the moon's orbit around its parent planet. We show that the electron influx patterns strongly depend on Callisto's location within the Jovian magnetosphere, while the ion patterns are more robust against changes to the moon's local environment. Key Points: We calculate the effect of Callisto's perturbed electromagnetic environment on energetic particle fluxes onto the top of the atmosphere Electron flux patterns are strongly affected by Callisto's plasma interaction, while ion fluxes are nearly uniform in the perturbed fields Fluxes onto the exobase are largest within the Jovian current sheet, despite strong field perturbations generated by the plasma interaction